Reliability of the intra and inter-test measures with universal goniometer and podalic arthrometer of the active range of ankle inversion and eversion - Ana Gabriela de Figueiredo Araújo; Germanna de Medeiros Barbosa; Roberta de Andrade Freire; Palloma Rodrigues de Andrade; José Jamacy de Almeida Ferreira; Heleodório Honorato dos Santos (Universidade de São Paulo, 2014)
The objective this study was to evaluate intra and inter-rater and inter-instruments reliability of ankle inversion and eversion active range of motion. The study included 100 healthy individuals (71 women and 29 men; ages: 21.32±2.83 years old; body mass: 60.40±4.95 kg; height: 1.66±0.04 m; and body mass index: 21.89±2.83 kg/m2), who were submitted to measurement of ankle inversion and eversion using the universal goniometer and podalic arthrometer. We used the intra-class correlation coefficient (ICC) and Pearson's test, considering a 5% significance level. The results of this study demonstrated one very strong intra-rater ICC (0.91≥0.99; p<0.01) and a strong inter-rater (0.61≥0.9; p<0.01) in both the first and second measurements, especially when measured with the podalic arthrometer (ICC>0.8; universal goniometer: ICC<0.8). The inter-instruments correlation was proved as being regular and significant (0.31≥r≤0.6; p<0.01) for all evaluators and evaluations. Both tested instruments can be used in physical therapy practice for measurements of ankle inversion and eversion due to the high reliability presented, regardless of the evaluator's previous experience, especially the podalic arthrometer when compared to the universal goniometer, which is probably due to the lower influence that the appraiser has on the instrument during measurements.